2007
DOI: 10.1038/sj.bjp.0707213
|View full text |Cite
|
Sign up to set email alerts
|

P2X receptor characterization and IL‐1/IL‐1Ra release from human endothelial cells

Abstract: Background and purpose: The pro-inflammatory cytokine, interleukin-1b (IL-1b), has been implicated in the pathogenesis of atherosclerosis, potentially via its release from vascular endothelium. Endothelial cells (EC) synthesize IL-1b in response to inflammatory stimuli, but the demonstration and mechanism of release of IL-1 from ECs remains unclear. In activated monocytes, efficient release of bioactive IL-1b occurred via activation of ATP-gated P2X 7 receptors (P2X 7 Rs). Activation of P2X 7 R in ECs from hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 59 publications
4
51
0
1
Order By: Relevance
“…However, activation of toll-like receptor receptors by lipopolysaccharide or other inflammatory stimuli markedly up-regulates P2X4R but does not alter P2X7R levels (Raouf et al, 2007). Conversely, there is high P2X4R expression (Yamamoto et al, 2006) and little or no P2X7R expression (Beigi et al, 2003) in noninflamed vascular endothelial cells (EC); P2X7R is increased when EC are exposed to inflammatory cytokines (Wilson et al, 2007). These observations suggest that the relative copy numbers of both P2X7R and P2X4R subunits will change in these various cell types at different stages of inflammatory activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, activation of toll-like receptor receptors by lipopolysaccharide or other inflammatory stimuli markedly up-regulates P2X4R but does not alter P2X7R levels (Raouf et al, 2007). Conversely, there is high P2X4R expression (Yamamoto et al, 2006) and little or no P2X7R expression (Beigi et al, 2003) in noninflamed vascular endothelial cells (EC); P2X7R is increased when EC are exposed to inflammatory cytokines (Wilson et al, 2007). These observations suggest that the relative copy numbers of both P2X7R and P2X4R subunits will change in these various cell types at different stages of inflammatory activation.…”
mentioning
confidence: 99%
“…The expression of both P2X7R and P2X4R is known to be regulated during proinflammatory activation of monocyte/ macrophages (Humphreys and Dubyak, 1998), microglia (Raouf et al, 2007), and endothelial cells (Ramirez and Kunze, 2002;Wilson et al, 2007). P2X7R is strongly expressed in resting macrophages and microglia, whereas P2X4R expression is modest.…”
mentioning
confidence: 99%
“…We have previously shown that icIL-1ra is released from endothelial cells [16,17]. To establish if modulation of cell cycle proteins by EC icIL-1ra is dependent upon binding to the cellsurface type 1 IL-1 receptor (IL-1R1), we measured 3 H thymidine incorporation in IL-1R1 deficient and wild-type MLEC following infection with 60 pfu/cell Ad5RSVicIL-1ra1 or Ad5RSVeGFP.…”
Section: Icil-1ra1 Suppresses the Anti-proliferative Effects Of Il-1b Inmentioning
confidence: 99%
“…P2 receptors are subdivided into eight G protein-coupled P2Y receptors (P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , P2Y 11 , P2Y 12 , P2Y 13 and P2Y 14 ), leading to a second messenger system cascade, and seven ionotropic P2X receptors (P2X1-7) that mediate permeability to Na + , K + and Ca 2+ [24]. Endothelial cells from different vascular beds express both P2Y and P2X receptors, among which P2Y 1 , P2Y 2 , P2Y 11 , [25,26], P2X1, P2X4 and P2X7 [25,[27][28][29] seem to be the main endothelial subtypes. Amongst the welldescribed physiological functions, both P2Y and P2X receptors stimulate endothelial NO production [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%